Distribution of Intestinal Parasites in Patients Admitted to University Hospital: Four Year Retrospective Review - Günbey, Fatma; Aşçı Toraman, Zülal (Galenos Publishing House, 2024)
Objective: In this study, it was aimed to examine the distribution of intestinal parasites detected in people who applied to the parasitology laboratory of Fırat University Faculty of Medicine between January 2018 and December 2021. Methods: Parasitological examination reports of a total of 24,432 patients who applied to the Parasitology Laboratory of Fırat University Faculty of Medicine between January 2018 and December 2021 were examined retrospectively for the presence of intestinal parasites. Results: A total of 24,432 (male: 12,887, 52.75%; female: 11,545, 47.25%) patients whose stool and cellophane tape samples were analyzed during the four-year period between January 2018 and December 2021 were included in the study. Intestinal parasites were found in 335 (1.4%) of the 24,432 patients examined. The most frequently detected parasite was Giardia intestinalis (n=149, 46.6%), followed by Entamoeba coli (n=123, 38.5%) and Enterobius vermicularis (n=28, 8.6%). When the distribution of parasite detection rates by years was examined, it was seen that the highest rate was in 2021 and the lowest rate was in 2019. Conclusion: Intestinal parasitic infections (IPE) are one of the most important public health problems in the world and in our country. Various factors such as the education level of the society, socio-economic status, infrastructure and climate affect the distribution of IPE. When we look at the distribution of parasites by years, it is 1.3% in 2018; 1.13% in 2019; 1.18% in 2020; In 2021, we found it to be 2.03%. We think that this increase in intestinal parasites is caused by the infrastructure and sheltering problems caused by the earthquake in our region. © 2024, Galenos Publishing House. All rights reserved.
Üniversite Hastanesine Başvuran Hastalarda Bağırsak Parazitlerinin Dağılımı: Dört Yıllık Retrospektif İnceleme
Keywords: earthquake; Giardia intestinalis; intestinal parasites; prevalence